2006
DOI: 10.1063/1.2357010
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency noise in Josephson junctions for superconducting qubits

Abstract: The authors have studied low-frequency resistance fluctuations in shadow-evaporated Al/ AlO x /Al tunnel junctions. Between 300 and 5 K the spectral density follows a 1 / f law. Below 5 K, individual defects distort the 1 / f shape of the spectrum. The spectral density decreases linearly with temperature between 150 and 1 K and saturates below 0.8 K. At 4.2 K, it is about two orders of magnitude lower than expected from a recent survey ͓D. J. Van 4 Decoherence due to external sources such as the measurement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
47
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 26 publications
16
47
2
Order By: Relevance
“…On the other hand, Eroms et al 22 measured resistance fluctuations in aluminum tunnel junctions: they found about 100 times lower noise power at 4.2 K, a linear temperature dependence, and saturation below 0.8 K, i.e., S ic (f ) = (1/100) × A can Ic I −2 c (T /4.2 K)/|f |. With T = 0.8 K, this gives a value about 2.5 times lower than what we observe.…”
Section: (F)mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Eroms et al 22 measured resistance fluctuations in aluminum tunnel junctions: they found about 100 times lower noise power at 4.2 K, a linear temperature dependence, and saturation below 0.8 K, i.e., S ic (f ) = (1/100) × A can Ic I −2 c (T /4.2 K)/|f |. With T = 0.8 K, this gives a value about 2.5 times lower than what we observe.…”
Section: (F)mentioning
confidence: 99%
“…These expressions reproduce the noise spectrum, with the use of correction factors, as explained in the following section (Eqs. [18][19][20][21][22][23][24].…”
Section: Cross-psd: White-noise Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fabrication process is usually not at all epitaxial quasiequilibrium growth, thus one has to expect the oxide layer to be non-crystalline and disordered [20,21]. We will take this into account by investigating rough superconducting tunnel junctions, where we assume that the junction additionally contains a few transport channels with very high transmission eigenvalues.…”
Section: B Rough Superconducting Tunnel Junctionsmentioning
confidence: 99%
“…Compared with the Ohmic case, the QPT of the SBM with sub-Ohmic spectral density, which has been used to model the 1/f noise [11] in quantum dots [12,13] and superconductor qubit systems [14,15], is more involved. Different methods from the sub-Ohmic SBM cannot even lead to a qualitatively consistent result.…”
Section: Introductionmentioning
confidence: 99%